Finerenone in Diabetic-Kidney Disease, Renal and Cardiovascular Outcome: A Meta-Analysis of Independent Trial Registries - Gracia, Felicita; Simanjuntak, Arya Marganda; Amanda, Samira; Mustika, Linda Ida; Juwanto, Juwanto; Sembiring, Ligat Pribadi; Karimi, Jazil; Harahap, Sari; Rosmaliana, Rosmaliana (Indonesian Journal of Kidney and Hypertension, 2025)
Background: Diabetic kidney disease (DKD) remains a frequent complication of type 2 diabetes, which significantly increases cardiovascular risk. Despite existing treatments, a substantial risk of disease progression still remains, leading to further exploration in Finerenone, a selective nonsteroidal mineralocorticoid receptor antagonist. Objective: This meta-analysis evaluates finerenone’s effects on the improvement of cardiorenal outcomes in DKD. Methods: A Systematic Review and Meta-Analysis (PROSPERO CRD420251122382) followed PRISMA guidelines. PubMed, ScienceDirect, and Epistemonikos utilized and used keywords “Finerenone AND Diabetes AND Chronic Kidney Disease AND Outcomes.” RCTs comparing finerenone to placebo in DKD, reporting renal or cardiovascular outcomes, were included. Data extraction covered study characteristics and outcomes. RevMan 5.4 analyzed data using a random-effects model. Risk of bias (RoB2) and certainty of evidence (GRADE-PRO) were assessed. Results: Three RCTs (19,027 participants) were included for renal outcomes, and two RCTs (13,026 participants) for cardiovascular outcomes. Finerenone significantly reduced the odds of sustained eGFR decline ≥40% (OR 0.83, p=0.0003) and≥57% (OR 0.86, p=0.0001), as well as the major composite kidney outcome (OR 0.76, p<0.0001). ESKD odds reduction (21%) was not statistically significant. For cardiovascular outcomes, finerenone significantly reduced hospitalization for heart failure (OR 0.78, p=0.0001). Trends towards reduced cardiovascular death (OR 0.88, p=0.09) were noted. Studies had low bias risk, and most outcomes showed moderate evidence certainty. Conclusions: Finerenone is associated with significant renoprotection and significantly reduces heart failure hospitalizations in DKD. Finerenone as an effective nonsteroidal mineralocorticoid receptor antagonist for comprehensive management, improving cardiorenal outcomes in this high-risk group.